Analysis of application of methods of recognition of patterns for exposure of electronic deliveries of publicities - Галла, Ю. В. (Problems of Informatization and Control, 2007)
In this article problem of using the methods of identify the patterns during automatically processing of e-mails for detection between them of unwanted advertising correspondence, so called SPAM. Review of existing scales of unwanted e-mails is presented; classification of method which are used by senders of SPAM is given; review of methods of evasion automatically filter systems, methods and algorithms of exiting anti-SPAM systems is give; using of adaptive method of identification the image data for processing of “graphic SPAM” is offered